Dimensions of the Political in Adjudication: A Case Study - Mańko, Rafał (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
Contrary to traditional accounts, which treat adjudication as the application of legal norms to the facts of a case, without any creative activity, the present paper assumes, following crtitical legal theory, that adjudication as a social practice belongs to the sphere of the political and involves judicial decision-making. The concept of the political is understood, following Chantal Mouffe, as the dimension of unalienable and inherent antagonism underlying any society. Any judicial decision, and especially one taken in a case where the court enjoyed a broad scope of discretion, influences a given social antagonism. However, as a prerequisite of a critical analysis of case-law it is necessary to identify the social antagonisms in question. To this end, the paper first analyses the very concept of an antagonism, highlighting its collective character, and then makes a tentative application of the concept to the European Court of Justice, attempting to identify the main types of social antagonisms which are subject to the Court’s jurisdiction.